A Nash bargaining-based cooperative planning and operation method for wind-hydrogen-heat multi-agent energy system. (15th January 2022) - Ma, Tengfei; Pei, Wei; Deng, Wei; Xiao, Hao; Yang, Yanhong; Tang, Chenghong
Abstract: Hydrogen production and clean heating from renewable power are promising methods to promote renewable energy consumption and reduce carbon emission. This paper is concentrated on the cooperative planning and operation problems of Wind-Hydrogen-Heat multi-agent energy system. A cooperative planning and operative model for the Wind-Hydrogen-Heating multi-agent energy system is proposed based on the Nash bargaining game theory. This cooperative model is transformed into two subproblems on the alliance planning and operation cost minimization problem and the payment bargaining problem. To protect the privacy of each participant, two distributed algorithms are proposed based on the Alternating Direction Method of Multipliers to solve the two subproblems. Finally, the effectiveness of the proposed cooperative model and distributed algorithms are demonstrated. Simulation results demonstrate that the proposed cooperative model can improve the benefits of both each participant and the cooperative alliance significantly. Furthermore, the wind power curtailment can be reduced through cooperation. And the decline of feed-in tariff of wind power will incentivize the cooperation of Wind-Hydrogen-Heat agents to improve their own benefits. Highlights: A Nash bargaining-based cooperative planning and operation incentive mechanism is proposed. The intractable cooperative planning and operation model is decomposed into two tractable subproblems. Two effective distributed algorithms are proposed to solve subproblems and protect privacy. Sensitivity of feed-in tariff is analyzed to study its effects on the cooperation issues.